2021
DOI: 10.1002/bse.2918
|View full text |Cite
|
Sign up to set email alerts
|

Circular economy practices and industry 4.0 technologies: A strategic move of automobile industry

Abstract: The fourth industrial revolution (IR4.0) toward automation and digitalization is the new trend among automobile production systems. Indubitably, the automobile industry has been scurrying in this revolution due to investment and governmental support availability. The current study examines the role of industry 4.0 on circular economy practices and supply chain capability to improve firm performance. Cross-sectional data were collected from 286 respondents through a closed-ended questionnaire.The adoption of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(81 citation statements)
references
References 103 publications
2
55
0
1
Order By: Relevance
“…It encompasses the ability of a firm to adopt industry 4.0 technologies such as blockchain and business analytics which help firms in making smart contracts, analyzing and enabling transparency, and creating integration among SC operations (Khan et al, 2021;Yu et al, 2021).…”
Section: Green Digitalization Capabilities (Gdc)mentioning
confidence: 99%
See 1 more Smart Citation
“…It encompasses the ability of a firm to adopt industry 4.0 technologies such as blockchain and business analytics which help firms in making smart contracts, analyzing and enabling transparency, and creating integration among SC operations (Khan et al, 2021;Yu et al, 2021).…”
Section: Green Digitalization Capabilities (Gdc)mentioning
confidence: 99%
“…The researchers have also elaborated that firms are adopting GPP because it helped firms in enhancing the quality of their product, sales, and good reputation among the customers. Moreover,Yu et al (2021) are of the view that GPP have a key role in adoption of financial performance. They have also indicated that firms can mitigate their adverse effect, efficiently utilize their resources, and enhance competitiveness through incorporating GnP in their operations.Regarding the effect of GPP on SCOP, the current study has stated an insignificant impact of GPP on SCOP.…”
mentioning
confidence: 99%
“…To get a sense of how the IoT will affect the economy, it is helpful to go back and review the history of how ICT has influenced economic growth. During the last three decades of research, a period that has seen a revolution in information technology, Yu et al (2021) famously advocated this topic in the field of economics. There have been two main approaches taken by economists to the problem: micro and macro.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Summarising, the local main paths show that most articles focus on conceptualising the CE and identifying its drivers and barriers, while few articles concentrate on the contribution of Industry 4.0 technologies to the acceleration of CE transition [ 9 , 11 , 34 , 92 , 118 , 131 , 162 , 180 ]. Therefore, future studies should assess how Industry 4.0 technologies effectively unlock the CE implementation, support the development of circular business models, and monitor product lifecycle [ 118 , 140 , 173 ].…”
Section: Findings Of Mpamentioning
confidence: 99%